Make Learning Fun sebagai Upaya Mahasiswa Kampus Mengajar dalam Pengelolaan Kelas Inovatif - Muharam, Suhari; Yusuf Sobri, Ahmad (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
Make Learning Fun is a strategy for kampus mengajar students' classroom management that focuses on creating an interesting and interactive learning environment for students. This approach aims to prevent boredom in the learning process. This study examines classroom management strategies implemented by students who are members of the Kampus Mengajar program at SDN 4 Bedahan Depok. The researcher used a qualitative approach with a case study research design. In this study, researchers used NVivo 12 Pro software to code data from the results of data collection of interviews, observations, and documentation. The findings of this study show that the implementation of strategies in classroom management through the Make Learning Fun program was the first time created by kampus mengajar students at SDN Bedahan 4 Depok. Students are able to think innovatively in classroom management by making the learning process not only transfer knowledge but also create a fun, interesting, interactive learning atmosphere according to the needs of students without eliminating aspects of learning objectives. The findings of this study can be described as follows: (1) Student Strategies in Classroom Management; (2) Student Implementation of Classroom Management; and (3) Make Learning Fun as a Student Strategy in Classroom Management.